Determinants of farmer's decision to transit to medium/larger farm through expansion of land area under commercial tree crop plantation in Nigeria. Issue 4 (2nd October 2022) - Aromolaran, Adebayo B.; Obayelu, Abiodun E.; Muyanga, Milu; Jayne, Thomas; Adelaja, Adesoji; Awokuse, Titus; Ogunmola, Omotoso O.; Osinowo, Olatokunbo H
ABSTRACT: Decision-making is central to farm management. This study assesses key factors influencing land allocation decisions of households with respects to tree crop cultivation in Nigeria. The study uses primary data collected electronically from a sample of 569 small and 495 medium-scale farmers in Ogun State.Tobit and Heckman regression models were estimated. The study finds that, farm households who have access to land markets and land tenure security, all-weather roads, agro-dealer services and better transportation services are more likely to cultivate tree crop fields and allocate a higher share of total farm holdings to tree crop enterprises. Farm households with more educated heads put larger area of land under commercial tree crop cultivation and those with larger off-farm income tend to cultivate less hectarage to tree crops. The share of farmland allocated to tree crops by male headed households is higher than the share by the female headed households. In addition, female and youth-headed households were found to be less likely to invest in commercial tree crop farming. Policies and intervention programs that would enhance access to land, agro-dealer services, all-weather roads, transportation services and security of land tenure could facilitate the redistribution of land in favour of commercial tree crops.